Pengaruh Bentuk Dan Dimensi Tapak Pondasi Terhadap Daya Dukung Pondasi Dangkal Akibat Beban Aksial Pada Tanah Pasir - Lingga Panji Subrata; S A Nugroho; Ferry ' Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The load distribution of shallow foundation spread out along the width of the foundation. Ultimate bearing capacity is defined as the maximum load that can be supported by the footing. Some form of shallow foundation were square, rectangular and circular shapes were they made to analyze the influence of the foundation over the same area of the shallow foundation bearing capacity due to axial loads on sandy soil. Variations foundation area of 100 cm2, 150 cm2 and 200 cm2. In the same area, the square shape can withstand greater load than in rectangular and circular shapes. Addition area will make 50-100% in weight-bearing capacity increased from 102,016 to 157,661% for squares, 135,751 to 228,497% for the rectangle and circle 187,413 to 341.259%. There are differences in the results of observation and empirical formula. Shape factors of squares and circles according to Mayerhof, Vesic and Hansen are the same. So, Terzaghi`s formula was similiar phenomenom with this research.Keywords : Shallow foundation, shapes, dimension, sand